FUCOIDAN FROM BROWN SEAWEED AND ITS BIOACTIVITY - Ellya Sinurat; Endar Marraskuranto (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
Fucoidan is a polysaccharide which substantially consists of L-fucosa and ester sulphate group and is mainly contained in brown seaweed. For the past ten years, bioactivity studies of fucoidan has been conducted. Recently, fucoidan has been examined for its application in drugs. In a couple of years, fucoidan structure was succesfully identified and its bioactivity was revealed. Fucoidan exhibits various bioactivities such as anticoagulant, antioxidant, anticomplementary, anti-inflamation, gastric protector, and blood lipid level control. This review gives some brief progress in isolation and bioactivity study of fucoidan from brown seaweeds.